2010
DOI: 10.1128/aac.00299-10
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Combination of Rifampin and Streptomycin for Treatment ofMycobacterium ulceransDisease

Abstract: We have evaluated the clinical efficacy of the combination of oral rifampin at 10 mg/kg of body weight and intramuscular streptomycin at 15 mg/kg for 8 weeks (RS8), as recommended by the WHO, in 160 PCRconfirmed cases of Mycobacterium ulcerans disease. In 152 patients (95%) with all forms of disease from early nodules to large ulcers, with or without edema, the lesions healed without recourse to surgery. Eight patients whose ulcers were healing poorly had skin grafting after completion of antibiotics. There we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
137
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(151 citation statements)
references
References 25 publications
10
137
2
2
Order By: Relevance
“…1,5,6 The efficacy of this treatment regimen has been confirmed in several studies. [7][8][9] Active lesions present with large focal clusters of extracellular acid-fast bacilli (AFB) and only minor leukocyte infiltration. 10,11 Antimicrobial therapy leads to massive leukocyte infiltration, which culminates in the development of ectopic lymphoid structures in the lesions.…”
Section: Introductionmentioning
confidence: 99%
“…1,5,6 The efficacy of this treatment regimen has been confirmed in several studies. [7][8][9] Active lesions present with large focal clusters of extracellular acid-fast bacilli (AFB) and only minor leukocyte infiltration. 10,11 Antimicrobial therapy leads to massive leukocyte infiltration, which culminates in the development of ectopic lymphoid structures in the lesions.…”
Section: Introductionmentioning
confidence: 99%
“…8,11,59,[61][62][63] This is important because it can be confused with recurrence. Paradoxical reaction is defined as an episode of new inflammation, with or without pus formation, with significant enlargement of a healing lesion during or after antibiotic treatment.…”
Section: Antibiotic Treatment Complicationsmentioning
confidence: 99%
“…This has been shown to result in healing of all forms of M. ulcerans disease with few exceptions. 8 expert advisors after a study showed that M. ulcerans organisms were still viable in early lesions excised after treatment for 2 weeks, whereas cultures were sterile when treatment was extended to 4 weeks, 8 weeks, or 12 weeks. 6 Further studies on antibiotic therapy are in progress.…”
Section: Antibiotic Therapymentioning
confidence: 99%
See 2 more Smart Citations